Heterosis studies for yield and its contributing characters in sesame (Sesamum indicum L.): Heterosis studies for yield and its contributing characters in sesame (Sesamum indicum L.) - P B WADIKAR; S J SONAWANE; S H PATIL (Journal of Oilseeds Research, 2020)
Heterosis for eleven characters was studied evaluation of parent and 28 F1 derived from crossing the 8 genotypes in half-diallel fashion. The analysis of variance revealed that significant differences existed among parents and hybrids for all characters. This validated that considerable amount of variability among experimental material. Five crosses viz., G-1 x IC-204025, LOCAL x AKT-101, LOCAL x AKT-306, LOCAL x YLM-17, AKT-306 x YLM-17 and G-1 x AKT-306 manifested significant and positive heterosis over better parent and both standard checks JLT-408 and Phule Til-1, respectively, for seed yield/plant. These crosses have been identified for exploitation of heterosis and also for utilization in future breeding programmes to obtain desirable transgressive segregants for the development of superior genotypes.